2012
DOI: 10.1016/j.jsat.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Two approaches to tailoring treatment for cultural minority adolescents

Abstract: At this time, compared with mainstream (Caucasian) youth, cultural minority adolescents experience more severe substance-related consequences and are less likely to receive treatment. While several empirically supported interventions (ESIs), such as motivational interviewing (MI), have been evaluated with mainstream adolescents, fewer published studies have investigated the fit and efficacy of these interventions with cultural minority adolescents. Additionally, many empirical evaluations of ESIs have not expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 104 publications
2
37
1
Order By: Relevance
“…Second, following the literature, which shows that MI consistent therapist skills are positively related to treatment outcomes for adolescents through adults (e.g., Barnett, Moyers, et al, 2014; Gaume, Magill, et al, 2014; Moyers, Martin, Houck, Christopher, & Tonigan, 2009), we predicted that therapists’ greater use of MI skills would relate to better treatment response (less substance use frequency and related problems) for both Hispanic and non-Hispanic youth at the three-month follow-up. Third, consistent with prior theoretical work, which suggests that different factors may be salient to Hispanic youth’s treatment response, thus necessitating examination of therapeutic processes and outcomes for Hispanic youth (Feldstein Ewing et al, 2012; Salvador, DeVargas, & Feldstein Ewing, in press), we hypothesized that therapists would show greater MI skills with non-Hispanic versus Hispanic youth.…”
Section: Introductionmentioning
confidence: 79%
“…Second, following the literature, which shows that MI consistent therapist skills are positively related to treatment outcomes for adolescents through adults (e.g., Barnett, Moyers, et al, 2014; Gaume, Magill, et al, 2014; Moyers, Martin, Houck, Christopher, & Tonigan, 2009), we predicted that therapists’ greater use of MI skills would relate to better treatment response (less substance use frequency and related problems) for both Hispanic and non-Hispanic youth at the three-month follow-up. Third, consistent with prior theoretical work, which suggests that different factors may be salient to Hispanic youth’s treatment response, thus necessitating examination of therapeutic processes and outcomes for Hispanic youth (Feldstein Ewing et al, 2012; Salvador, DeVargas, & Feldstein Ewing, in press), we hypothesized that therapists would show greater MI skills with non-Hispanic versus Hispanic youth.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, little is known about whether minority youth fare better in certain settings or programs. [12] Studies with small, selective samples, suggests minority youth have lower retention and are less likely to complete treatment overall. [13,14]…”
Section: Introductionmentioning
confidence: 99%
“…These individuals may benefit from more directive or change-focused strategies. Using the PRQ in this way may improve delivery of MI to Hispanic/Latino individuals by showing when clients would benefit from client-centered strategies versus from prescriptive strategies, which may improve the consistency between the intervention and clients’ needs (Feldstein Ewing et al, 2012). Seemingly contradictory responses on the PRQ could also inform the clinical approach with adolescents, such as adolescents with high levels of both Readiness and Treatment Resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Also, Motivational Enhancement Therapy matched or outperformed other active treatments for Hispanic/Latino individuals (Carroll et al, 2009). It is argued that MI is fitting for Hispanic/Latino individuals (and other racial/ethnic minorities) due to client-centered elements that facilitate the ability for therapists to understand diverse worldviews (Feldstein Ewing, Wray, Mead, & Adams, 2012; Miller et al, 2007). However, it was found that therapists deliver MI less competently with Hispanic/Latino adolescents than with non-Hispanic/Latino adolescents and that the poorer delivery was associated with less responsiveness to treatment (Feldstein Ewing, Gaume, Ernst, Rivera, & Houck, 2015).…”
Section: Introductionmentioning
confidence: 99%